Photovoltaic technologies photo-thermal challenges: Thin active layer solar cells significance - K. Ghosh, Bablu; Hasanuzzman, M.; Saad, Ismail; Mohamad, K.A.; Hossain, Mohammad Kamal (Elsevier, 2023)
Massive energy demand and source of energy usages is the key root of global emission and climate change. Solar photovoltaic (PV) is low carbon energy technology currently 3.2% share of global electricity supply. The rapid progress of solar PV is vastly related to increase energy efficiency and lessening of active materials usage. This paper solar PV present significance and most prospective PV materials technical challenges are reviewed for its future advancement. Among the challenges solar energy absorption-related dynamic photo-thermal effect on cells or modules is vital. Transparent passivation contact materials with lower temperature coefficient (TC) and thin active layer resulted in lowering both dynamic photo-thermal outcome and optical to electrical energy gap. Thin active layer minor bulk recombination and sub-band parasitic absorption lessening purpose transparent conductive materials (TCM) based proper band barrier heterointerface is impending. It can optimize desired band absorption and photo-coupling with selective carrier induces greater efficiency. Earlier research though explains it on carrier selectivity prejudice, but how it can lessen the near infrared band optical and associated thermal influence is essential to illustrated. Passivation and TC interrelations hence, field related drift is control over diffusion process loss in advanced bifacial and thin active layer PV technology. Loss lessening pathways thin wafer-based Si, thin film CdTe, organic and perovskite photo coupling with advanced TCM, thus, Si/CdTe and Si/perovskite tandem cells along with OSC building integrated transparent photovoltaic technologies advancement pathways are reported.